AGING WITH VISION LOSS: EXPLORING EVERYDAY ACTIVITY CHALLENGES AND OPPORTUNITIES FOR TECHNOLOGY INNOVATION. (20th December 2022) - Remillard, Elena; Koon, Lyndsie; Mitzner, Tracy; Rogers, Wendy
Abstract: Vision loss can impact the health of older adults on multiple domains, including physically (e.g., mobility challenges), psychologically (e.g., depression), and socially (e.g., isolation). Older adults with vision loss, and particularly those with long-term vision loss, are likely to experience challenges in performing Instrumental Activities of Daily Living (IADLs), as these activities often require abilities like reading, fine motor movements, and navigating. We conducted structured interviews with 60 older adults aged 60-79 with vision loss for at least 10 years about their challenges with select IADLs (e.g., household tasks, transportation, shopping, finances, and managing health). An analysis of in-depth interview data revealed specific challenge themes associated with engaging in different IADLS, such as challenges with accessibility, physical limitations, assistance from others, communication, and finances. Findings highlight opportunities for technology solutions to support IADL participation and independence for people aging with vision loss.